Biodiversity indicators for breeding passerines in a multiple-cuckoo system in China: A comparison of cuckoos and raptors - Sidan Lin; Wei Liang (Global Ecology and Conservation)
In the Anthropocene, monitoring and assessing biodiversity and taking conservation measures due to declining biodiversity is an urgent task. However, resource and time constraints make it unfeasible for biodiversity surveys to cover all taxonomic groups; hence, finding alternative shortcuts, such as biodiversity indicators, is necessary. We compared the effectiveness of obligate brood parasitic cuckoos as biological indicators with raptors, a previously recognized indicator species, across ecogeographic regions of China based on different components of biodiversity (e.g. taxonomic, phylogenetic, and functional diversity). The results showed that the number of cuckoo species had significant positive correlations with taxonomic diversity (TD), phylogenetic diversity (PD), and functional richness (FRic) of passerines but no significant correlation with evolutionary distinctness (ED) or evolutionary distinct and globally endangered (EDGE). In contrast, raptors showed a significant positive correlation only with EDGE. The greater number of factors associated with cuckoos suggests that they exhibit superior performance as biodiversity indicators compared to raptors. However, this does not undermine the significance of raptors as indicators. Selecting the indicator is context-dependent, with cuckoos being suitable for routine surveys, monitoring overall avian diversity, and raptors being suitable for assessing the status of endangered birds, conducting conservation measures, and measuring their effectiveness. We anticipate cuckoos to gain more public attention as a paradigm of biodiversity indicators and be put into practice.